Ankle Blocks Can Minimize the Need for Opiates in Forefoot Surgery. Issue 4 (16th October 2019) - Pountos, Ippokratis; Tellisi, Nazzar; Gupta, Pawan
Category: Midfoot/Forefoot Introduction/Purpose: Postoperative pain following forefoot surgery is often difficult to control with oral medications requiring large doses of opioid analgesia. Regional anaesthesia is an alternative approach that reduces the need for general anaesthetic and can provide adequate pain control in the immediate postoperative period. The purpose of this study was to analyse the effectiveness of ankle blocks in patients undergoing forefoot surgery. Methods: The authors prospectively included 22 consecutive patients undergoing forefoot surgery in the last semester of 2018. The blocks were performed by a senior anaesthetist with bupivacaine or levobupivacaine to posterior tibial (6-10mls), saphenous (2-4mls), superficial and deep peroneal (4-6mls) and sural nerve (4-6mls). Collected data included demographic information, pain scores and postoperative prescriptions, satisfactions questionnaires and post-operative outcomes. Results: The study group included 22 patients with a mean age of 50 years (range 23-81). There were 16 females and 6 males, overall BMI was 26, 35 and the majority of patients were fit and well (86% ASA 1 or 2). The blocks lasted for an average 45 hours (range 20-92). In terms of the post-operative analgesia needs, 14% of the patients required no further analgesia, 45% required paracetamol and ibuprofen and 41% required dihydrocodeine. All 22 patients were highly satisfied with the analgesia provided, no complications were reported and no re-admissions occurred. Conclusion: Ankle blocks were a safe and reliable anaesthetic choice providing highly effective perioperative pain management in patients undergoing elective orthopaedic forefoot procedures. Patients with ankle block had better pain management, decreased opioid requirements and high satisfaction rates.